The effect of differing patterns of childhood body mass index gain on adult physiology in American Indians. (September 2015) - Thearle, Marie S.; Votruba, Susanne B.; Piaggi, Paolo; Muller, Yunhua L.; Hanson, Robert L.; Baier, Leslie J; Knowler, William; Krakoff, Jonathan
<x xml:space="preserve">Abstract</x> Objective Identifying groups of individuals with similar patterns of body mass index (BMI) change during childhood may increase understanding of the relationship between childhood BMI and adult health. Methods Discrete classes of BMI z‐score change were determined in 1, 920 American Indian children with at least four non diabetic health examinations between the ages of 2 and 18 years using latent class trajectory analysis. In subsets of subjects, data were available for melanocortin‐4 receptor (MC4R) sequencing; in utero exposure to type 2 diabetes (T2D); or, as adults, oral glucose tolerance tests, onset of T2D, or body composition. Results Six separate groups were identified. Individuals with a more modern birth year, an MC4R mutation, or in utero exposure to T2D were clustered in the two groups with high increasing and chronic overweight z‐scores (P < 0.0001). The z‐score classes predicted adult percent fat (P < 0.0001, partial r2 = 0.18 adjusted for covariates). There was a greater risk for T2D, independent from adult BMI, in three classes (lean increasing to overweight, high increasing, and chronic overweight z‐scores) compared to the two leanest groups (respectively: HRR= 3.2, P = 0.01; 6.0, P = 0.0003; 11.6, P < 0.0001). Conclusions Distinct patterns of childhood BMI z‐score change associate with adult adiposity and may impact risk of T2D.